PERAN RUMAH PINTAR TUNAS HARAPAN KABUPATEN HULU SUNGAI UTARA DALAM PEMBERDAYAAN EKONOMI MASYARAKAT - Lily Misliani; Irawanto I; Riky Welli Saputra (Administraus, 2022)
Abstract : The purpose of this research is to analyze: (1) the role of the Rumah Pintar Tunas Harapan in empowering the community's economy, (2) the constraints concerning the role of the Rumah Pintar Tunas Harapan in the community's economic empowerment, and (3) solutions to overcome the obstacles concerning the role of the Rumah Pintar Tunas Harapan. in community economic empowerment. This research uses a qualitative approach. with descriptive method. Data were obtained from the management of the Rumah Pintar Tunas Harapan as many as 10 people (informants) and the community involved in the activities of the Rumah Pintar Tunas Harapan, Hulu Sungai Utara Regency as many as 7 (seven) people. Relevant data collection techniques and tools. The method used for the data collection process in this research is the triangulation process, namely: Interviews, Observations and Documents. Analysis of existing data used descriptive analytical method. The results showed (1) the Rumah Pintar Tunas Harapan in empowering the community's economy as a service according to the needs of the community itself. The role of the Rumah Pintar Tunas Harapan is that the community gains improvement, skills, talent development, and activities that are fun to read, so that the library has a role as a means to achieve that goal. Rumah Pintar Tunas Harapan activities include; Computer Centers and Sewing Centers, (2) Obstacles concerning the role of the Rumah Pintar Tunas Harapan in community economic empowerment Provision or improvement of learning facilities and tools for the development of existing centers in the Smart House, guidance/training to increase the capacity of managers and tutors in enhancing the role of institutions and learning services in accordance with the existing centers at the Smart House, documenting the process of measuring the results of the implementation of the Smart Home mentoring activities periodically during the implementation period and at the end of the mentoring activities. Institutions need to design and prepare instruments to measure the progress of activities and learning outcomes of students involved in organized learning, (3) Solutions achieved to overcome the role of the Rumah Pintar Tunas Harapan in community economic empowerment by increasing active community participation, improving the quality of implementers , financing and increasing sectoral cooperation so that program objectives can be carried out properly. Keywords: Role, Smart House, Empowerment, Economy Abstrak : Tujuan dari penelitian ini adalah menganalis: (1) Peran Rumah Pintar Tunas Harapan dalam pemberdayaan ekonomi masyarakat, (2) kendala yang menyangkut Peran Rumah Pintar Tunas Harapan di dalam pemberdayaan ekonomi masyarakat, dan (3) solusi mengatasi kendala yang menyangkut peran Rumah Pintar Tunas Harapan di dalam pemberdayaan ekonomi masyarakat. Penelitian ini menggu akan pendekatan kualitatif. dengan metode deskriptif. Data diperoleh dari Pengelola Rumah Pintar Tunas Harapan sebanyak 10 orang(Informan) dan Masyarakat yang terlibat dalam aktivitas kegiatan Rumah Pintar Tunas Harapan Kabupaten Hulu Sungai Utarasebanyak 7 (tujuh) orang. Teknik dan alat pengumpulan data yang relevan. Metode yang digunakan untuk proses pengumpulan data dalam penelitian ini adalah dengan proses trianggulasi, yaitu: Wawancara, Observasi dan Dokumen. Analisis data yang sudah ada digunakan metode deskriptif analitik. Hasil penelitian menunjukkan (1) Rumah Pintar Tunas Harapan di dalam pemberdayaan ekonomi masyarakatsebagai layanan sesuai kebutuhan masyarakat itu sendiri.Peranan Rumah Pintar Tunas Harapan adalah masyarakat memperoleh wawasan pengetahuan, keterampilan, pengembangan bakat serta kegiatan yang menyenangkan membaca, sehingga keberadaan perpustakaan mempunyai peranan sebagai sarana untuk mencapai tujuan tersebut. Kegiatan Rumah Pintar Tunas Harapan Meliputi ; Sentra Komputer dan Sentra Menjahit, (2) Kendala yang menyangkut peranan Rumah Pintar Tunas Harapan di dalam pemberdayaan ekonomi masyarakat Penyediaan atau peningkatan sarana dan alat belajar bagi pengembangan sentra yang ada di Rumah Pintar, bimbingan/pelatihan peningkatan kapasitas pengelola dan tutor dalam meningkatkan peran lembaga dan layanan pembelajaran sesuai dengan sentra yang ada pada Rumah Pintar, pendokumentasian proses mengukur hasil penyelenggaraan kegiatan pendampingan Rumah Pintar secara berkala selama masa penyelengaraan dan pada akhir kegiatan pendampingan. Lembaga perlu merancang dan menyiapkan instrumen penilaian untuk mengukur kemajuan kegiatan pendampingan dan hasil belajar peserta didik yang terlibat di dalam pembelajaran/pelatihan yang diselenggarakan, (3) Solusi yang ditempuh untuk mengatasi kendala peran Rumah Pintar Tunas Harapan Di Dalam pemberdayaan ekonomi masyarakatdengan meningkatkan partisipasi masyarakat secara aktif, meningkatkan kualitas petugas pelaksana, pembiayaan yang cukup serta meningkatkan kerjasama secara sektoral dengan maksud agar tujuan program dapat terlaksana dengan baik. Kata Kunci : Kompensasi Finansial Langsung, Gaji, Tunjangan, Insentif, Upah Minimum Kota